COMPARISON OF LEAVES AND BARK MANGKOKAN (Nothopanax scutellarium) EXTRACTS AGAINST THE DEATH OF HOUSE FLIES (Musca domestica) - Darmadi; Harni Sepriyani (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2020)
Flies (Musca domestica) are vectors of disease that can transmit to humans. Generally, these flies controlled by using chemical insecticides. Excessive use of insecticide causes resistance and environmental pollution. The alternative way in fly control is to use natural ingredients from the extract of mangkokan stem bark and leaves (Nothopanax scutellaria). This study aims to determine the ratio of fly mortality after administration of ethanol extract of bark and methanol extract of mangkokan leaves (N. scutellarium). The method used in this study is a post-test only control group design. The average mortality rate of house flies using ethanol extract of mangkokan stem bark (N. scutellarium) was 5 for 55 minutes while methanol extract of mangkokan leaves (N. scutellarium) was 5 for 135 minutes with a p-value of 0.374 (p>0.05). It concludes that there is no significant difference in fly mortality with the ethanol extract of stem bark and methanol extract of mangkokan leaves (N. scutellarium). Result of this study shows that the ethanol extract of stem bark and mangkokan leaf extract (N. scutellarium) are equally potential natural insecticides.